Glued laminated timber: Potential on building, from undergraduate to industrialization - Pauli, Beatriz Alineri; Azambuja, Maximiliano dos Anjos; Oliveira Neto , Luttgardes de (Technical and Scientific Journal Green Cities, 2021)
The Glued Laminated Timber (Glulam) technique presents a lot of features and benefits over other constructive materials and the most diverse applications. It has become an important feedstock in construction and it can be said that this material brings even more advantages than solid wood. The Glulam is best known for its use on constructive elements (beams, pillars, casings, roofing structures, etc.), but little is mentioned about the technique’s application on adornments or furniture. In Brazil, the knowledge about the qualities of this material is even less spread. This work intends to search for the reasons why the Glulam is scarcely used in Brazil, as it does to show the material’s potential on not only structural elements, by the making of an architecture project of a Living Area. Keywords: Glued Laminated Timber, Glulam, building.